Peningkatan Kemampuan Berhitung dengan Menggunakan Media Abakus pada Siswa Kelas I Sekolah Dasar - Desy Alfitriani; Muhammad Naji Al-Maruf; Muhammad Hendrik Prayitno (EduStream: Jurnal Pendidikan Dasar, 2022)
This study is intended to propagate a learning medium of abacus. The abax comes from Greek, which AIDS arithmetic to make numerical operations easier. This learning media is perfect for simplicity in both low and high classes in elementary school or elementary school. Elementary school. This type of research is class action research (PTK). The English term is classroom action research (car), a research activity carried out in class. Class action research (PTK) is a study activity that involves a class action that is carried out to solve the learning problems faced by teachers, improve and produce learning and try new things in learning for the improvement and the data-collection study that is used is interviews, tests, and observations. The validation obtained by 83.3% means that abacus learning media can be applied. Based on the data obtained, it could be concluded that the knowledge or cognition of the class I SDI al-khoiriyah class increased with the application of the learning media abacus so that the action carried out in the study was said to be successful without further action.